Unsur Utopia dalam 3 Novel Kontemporer Jepang Karya Jiro Akagawa - Nalti Novianti (Humaniora, 2010)
The concept of Utopia that exist in three Jiro Akagawa’s Japanese contemporary novel, described the condition of Japan society nowadays. In the relationship concept that relies on hierarchy and closeness relationship between persona in Japan, Akagawa tried to think out of the box. Akagawa’s novel is a mystery novel focusing on society, mostly about the characteristic that influenced  by the Uchi and Soto concept.  These concepts made Japan society divided into ”inner group” and ”outer group”. Also, this concept made the Japan society not very active in making a relationship outside her/him self. In the style of Akagawa’s satire, he described this idea in his novels to convey the message to the reader.